EFEKTIVITAS PELAKSANAAN DIVERSI TERHADAP ANAK BERHADAPAN DENGAN HUKUM DI KABUPATEN KUANTAN SINGINGI - Lesti Hardianti; Erdianto Erdianto; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Not all cases of delinquent children must be resolved through formal judicialchannels, objective and fair law is required to be able to offer alternative ideas that are morehumane and simply do not place penal means as the primum remedium. This conception givesbirth to novelty, and provides an alternative solution using a justice approach in the bestinterests of the child and taking into account justice for victims, known as an approach basedon the principles of restorative justice. This concept is believed to be able to fulfill proportionaljustice for both parties when in fact the child is the perpetrator. On the other hand, one of thereasons that other solutions and approaches are needed for children in conflict with the law isthat correctional institutions are full, therefore a diversion policy is needed to overcome this asan alternative idea. Understanding that keeping children away from the criminal justiceprocess is important because this is part of efforts to protect children's human rights as statedin the Convention on the Rights of the Child which provides opportunities for the diversionprocess carried out by the Police and Public Prosecutor as well as other officials who have theauthority to keep them away. children from the judicial process. However, the fact is thatdiversion does not always produce a deterrent effect for perpetrators, there are still childrenwho re-commit criminal acts after being given diversion.This research is sociological legal research. This is based on research whichemphasizes legal aspects (legislation) relating to the main issues to be discussed, linked toreality on the ground. This research uses primary data sources consisting of primary,secondary and tertiary legal materials.From the results of the research and discussions carried out, several conclusionswere obtained, namely: First, the implementation of diversion in Kuantan Singingi Regencywas not optimal and effective. Law enforcers who are not yet ready to carry out statutoryorders, the absence of guidance institutions such as Bapas and the absence of further guidancefor children after giving diversion. Second, the creation of ideal and maximum diversity andincluding restorative justice in it, can be achieved through various efforts. Such as providingoutreach, input and understanding to all parties (stakeholders) involved, forming Bapas orinstitutions that can carry out the roles and functions of Bapas to monitor the implementationof diversion which has not existed in Kuantan Singingi Regency, which is actually an orderfrom the law.Keywords: Children Facing the Law – Diversion – Crime